THE EFFECT OF MAKING SUMMARY ON STUDENTS’ WRITING ACHIEVEMENT OF OF THE STUDENTS OF SMA SWASTA MELATI BINJAI - Juliantina Juliantina - (Jurnal Serunai Bahasa Inggris, 2019)
This research aims to know the effectiveness of making summaries in student achievement in writing and to find out if making a summary is able to improve student performance in writing in the grade ten students private high school Melati Binjai 2017/ 2018. In this study, apply the creation summary as an independent variable (X) and student learning achievement in writing as a dependent variable (Y), with hypotheses: there is a significant influence of the implementation of making summaries on achievements Students in writing in grade ten students from 2017/2018 grade ten from private SMA Melati Binjai. The population of this research is the XI-grade private high school student Melati Binjai in 2017/1988 consisting of 30 students. Samples taken using all sampling, the total sample is 30 students. Authors use tests as data collection instruments. Data is analyzed by using the test-t formula. Based on data analysis, it was found that the value T-observed (to) higher than the T-table value, (tobserved = 23.2 > Ttable = 2.04). Therefore, hypotheses submitted by the author are accepted. In other words, there is a significant influence of the implementation of making summaries on student achievement in writing.